DOES AQUASCAPE HAVE THE ABILITY TO PROVIDE THERAPY? - Sperico Michael Elden,; Ahmad Fauzan Badiuzaman ,; Mohamad Farhan Azmi,; Nik Mohd Shah Nik Mohd Nor,; Farhan Faat, (Journal of Islamic, Social, Economics and Development, 2023)
Even though aquariums are well-known and have physiological benefits, the term aquascape in aquarium appears to be unfamiliar to Malaysians. Aquascape has recently gained popularity as a hobby in Malaysia. This activity, also known as underwater gardening, entails creating a landscaped area with a conspicuous natural or constructed aquatic feature, and artfully arranging aquatic plants, as well as rocks, stones, cavework, or driftwood, in an aquarium in an aesthetically pleasing manner. Stress is unavoidable in both the household and the workplace. As a result of its impact on emotions and its negative connotation, excessive tension may result in an unhealthy way of life. It is well known that some people visit a fish shop to relax, and aquascape therapy may be able to reduce tension. This study empirically investigates the perspective of aquascape on the therapeutic effect of aquarium viewing. Consequently, based on the current circumstance, it could be an excellent time to investigate further. This study empirically examines the perspective of 114 customers regarding aquascape as the therapeutic effect of observing aquariums, using a local fish store as the study context. The respondent's insightful perspective on the investigation issue could make a positive contribution to pyhsiological-specific academic perspectives